Ferrocenyl conjugated oxazepines/quinolines: multiyne coupling and ring–expanding or rearrangement - Lei, Yu; Bao, Li; Hu, Qiong; Zhang, Ke; Zong, Lingli; Hu, Yimin (Frontiers in Chemistry, 2024)
Ferrocenyl conjugated oxazepine/quinoline derivatives were presented through the reaction of hexadehydro-Diels–Alder (HDDA) generated arynes with ferrocenyl oxazolines under mild conditions via ring-expanding or rearrangement processes. Water molecule participated in this unexpected rearrangement process to produce quinoline skeletons, and DFT calculations supported a ring-expanding and intramolecular hydrogen migration process for the formation of oxazepine derivatives. Two variants of this chemistry, expanded the reactivity between ferrocenyl conjugated substances and arynes, further providing an innovative approach for the synthesis of ferrocene derivatives.